Effectiveness and Safety of Nonmedical Switch From Adalimumab Originator to SB5 Biosimilar in Patients With Inflammatory Bowel Diseases: Twelve-Month Follow-Up From the TABLET Registry. Issue 1 (11th February 2021) - Tapete, Gherardo; Bertani, Lorenzo; Pieraccini, Alberto; Lynch, Erica Nicola; Giannotta, Martina; Morganti, Riccardo; Biviano, Ivano; Naldini, Sara; Mumolo, Maria Gloria; De Nigris, Francesca; Calella, Francesca; Bagnoli, Siro; et al.
Abstract: Background: Few data are currently available about SB5 in inflammatory bowel diseases (IBD). The aim of this study was to assess the effectiveness and safety of SB5 in a cohort of patients with IBD in stable remission switched from the adalimumab (ADA) originator and in a cohort of patients with IBD naïve to ADA. Methods: We prospectively enrolled patients with IBD who started ADA treatment with SB5 (naïve cohort) and those who underwent a nonmedical switch from the ADA originator to SB5 (switching cohort). Clinical remission and safety were assessed at baseline and at 3, 6, and 12 months. In addition, in a small cohort of patients who were switched, we assessed the ADA serum trough levels and antidrug antibodies at baseline, 3, and 6 months. Results: In the naïve cohort, the overall remission rate at 12 months was 60.42%, whereas in the switching cohort it was 89.02%. Fifty-three (36.3%) patients experienced an adverse event, and injection site pain was the most common; it was significantly more frequent in the switching cohort ( P  = 0.001). No differences were found in terms of ADA serum trough levels at baseline, 3, and 6 months after switching. No patient developed antidrug antibodies after the switch. Conclusions: We found that SB5 seemed effective and safe in IBD, both in the naïve cohort and in the switching cohort. Further studies are needed to confirm these data in terms of mucosal healing.